Analisis Kebijakan Penataan Dan Penetapan Daerah Pemilihan DPRD Kabupaten Deli Serdang Pemilu Tahun 2019 - Syaiful Azhar; Tonny P. Situmorang; Bengkel Ginting (PERSPEKTIF, 2023)
This study aims to analyze the process and results of the formation of the electoral district of the DPRD of Deli Serdang Regency in order to find out and ascertain how far the principles of forming electoral districts are applied. This research use desciptive qualitative approach. Data collection techniques in this study consisted of interviews, observations as primary data and collection of scientific references, government documents, general references and statistical data as secondary data. The results of the study found that the process of compiling, arranging and determining the electoral districts for the Members of the Deli Serdang Regency DPRD had been fully regulated through KPU Regulations and DecreesThe principle of arrangement of electoral districts that is regulated in regulations and also that is implemented empirically is not fully in line with the meaning of the principle of arrangement of electoral districts which is known theoretically. The existence of restrictions on the maximum and minimum number in determining seats in representative institutions results in inequality in the value of votes nationally or at the provincial level between districts/cities in their territories.